Case Report: Hemolytic anemia secondary to infliximab treatment in a patient with ulcerative colitis - Bevivino, Gerolamo; Scarozza, Patrizio; Di Fonzo, Michela; Zerboni, Giulia; Iacopini, Federico (Frontiers in Medicine, 2025)
Infliximab, a monoclonal antibody targeting tumor necrosis factor-alpha (TNF-α), is widely used in treating inflammatory bowel diseases (IBD), including ulcerative colitis (UC). While generally well-tolerated, infliximab is associated with rare but significant adverse effects, including autoimmune hemolytic anemia (AIHA). This report describes the case of a 54-year-old male diagnosed with UC, who developed hemolytic anemia secondary to infliximab therapy after 1 year of treatment. During the infusion preceding the onset of anemia, the patient experienced a severe infusion reaction characterized by urticaria, bronchospasm, chills, fever, and pulsating headache. Laboratory findings confirmed hemolytic anemia with a positive direct and negative indirect Coombs tests. The patient responded well to corticosteroid therapy (prednisone at 1 mg/kg/day for 30 days) and stopping anti-TNF-α, with hemoglobin levels improving from 7.2 g/dL at presentation to 14.6 g/dL after 1 month. AIHA should be considered an uncommon but serious complication of infliximab therapy, necessitating careful monitoring, especially in patients treated for gastrointestinal indications. This case underscores the importance of recognizing and managing infusion-related complications of biologic therapies.